Ageing Populations and Intergenerational Risk-sharing in PAYG Pension Schemes - Agneta Kruse (Lund University, School of Economics and Management, Department of Economics, 2002)
The purpose of this paper is to compare pension schemes with respect to their intergenerational redistributive effects caused by economic and demographic changes. It is shown how these effects depend on the specific design of the pension scheme, with special attention devoted to the indexation problem. There is a potential trade-off between financial stability of the pension system and a "desired" distribution between generations. A buffer fund is often seen as the remedy to demographic strain and potential conflict. Therefore, the possibility of accumulating (and de-cumulating) a buffer fund is included. A lifecycle perspective is applied and the risk-sharing is measured by different generations' rate of return. The analysis is carried out within the framework of an over-lapping generation model in the setting of a stylised economy.
Keywords: D30; H55; J14; J26; 330; Notional defined contribution pension systems; demographic changes; indexing; intergenerational risk-sharing